Determinants of Using Gadget to Concentration, Complaints of Eye Fatigue and Student Learning Motivation at SMKN 7 Malang - Naryaning, Rohmahtun; Katmini, Katmini (Journal for Quality in Public Health, 2021)
The development of information and communication technology brings an influence on many fronts, is no exception in the world of education. Including the use of gadgets that increasingly exist in the world of education. But the use of gadgets must also be monitored by the duration, frequency and intensity that support concentration, reduce eye fatigue complaints and motivation to learn for the better. The purposes of this study are to explain the influence of duration, frequency and intensity of gadget use on student concentration, eye fatigue complaints, students learning motivation at SMKN 7 Malang. This research design uses a correlative study with a quantitative approach. The research subjects were 195 students. Data collection techniques using a questionnaire. The data analysis technique used multiple linear regression analysis. The results of this research indicate that: there was a negative influence of duration, frequency, and intensity of using gadget on student concentration at SMKN 7 Malang. There was a positive influence of duration, frequency, and intensity of using gadget on student eye fatigue complaints at SMKN 7 Malang. There is a negative influence of duration, frequency, and intensity of using gadget on students learning motivation at SMKN 7 Malang. This study shows that there is a need for health promotion so that students reduce the duration, frequency of using gadgets as an effort to increase concentration, prevent eye fatigue and increase learning motivation.